Organizational Supports and Technostress of Civil Servants: The Mediator Effects of TAM - Dian Dwi Nur Rahmah; Netty Dyan Prastika; Reza Wardhana; Hardiansyah; Firjatullah (Psyche 165 Journal, 2025)
The SIKAP IDAMAN application as a digital innovation in civil service management, providing access to daily performance reports (LKH), performance data, and employee discipline mapping. However, its implementation has presented psychological challenges, particularly technostress among employees. This study aims to explore the influence of perceived organizational support and technology acceptance on technostress among civil servants in the Kutai Kartanegara Regency Government. A quantitative approach was employed, involving 36 employees from the Inspectorate Office who actively use the SIKAP IDAMAN application. Mediation analysis was conducted using JASP software version 0.14.1.0 to examine the relationships between variables. The results show that perceived organizational support significantly influences technostress through technology acceptance (p = 0.036). Perceived organizational support also has a direct negative effect on technostress (p = 0.000) with a path coefficient of -0.281 (low category, f² = 0.111). Furthermore, organizational support significantly influences technology acceptance (p = 0.000) with a path coefficient of 0.849 (high category, f² = 2.584). Technology acceptance also negatively affects technostress (p = 0.031) with a path coefficient of -0.448 (moderate category, f² = 0.154). These findings highlight the importance of technology acceptance as a mediating factor in reducing technostress, and emphasize the critical role of organizational support in facilitating successful technology adaptation among civil servants. Keywords: technostress, perceived organizational support, technology acceptance